Analisis Pengaruh Kompetensi Sumber Daya Manusia terhadap Kualitas Pelayanan Publik di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Ogan Komering Ilir - Nurmansyah, Andri; Heriyanto, Heriyanto (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to analyze the influence of human resource competency on the quality of public services at the Population and Civil Registration Service of Ogan Komering Ilir Regency. The research method used was a survey by distributing questionnaires to users of the Population and Civil Registration Service. The collected data was analyzed using regression techniques. The results of the research show that human resource competency has a significant positive influence on the quality of public services at the Population and Civil Registration Service of Ogan Komering Ilir Regency.